All dimensions Wiki
Advertisement
All dimensions Wiki

do thing below to get my number

f(0)n = n+1.

f(1)n = n*2

f(2)n = n^2

f(3)n = n^^2.

f(4)n = n^^^2.

overall, f(x)n is equal to n{x-1}n, except for f(1)n and f(2)n.

f(0,2)x(n) = f(x)n

f(1,2)x(n) = f(f(x)n))n

f(y,2)x(n) = f(f(f(f(f......y+1 layers of f(#)n.........f(x)n)n)n)n.......n)n

f(0,3)x(n) = f(x,2)x(n)

f(1,3)x(n) = f(f(0,2)x(n),2)x(n)

f(y,3)x(n) = f(f(f(f.....y+1 f's....f(0,2)x(n))x(n))x(n))....x(n))x(n))x(n)),2)x(n)

f(y,z)x(n) = f(f(f(f(f.........y+1 f's.......f(0,z-1)x(n))x(n))x(n)).....x(n))x(n)),2)x(n)

f(y,z,m)x(n) = f(f(f(f......y+1 f's.........f(0,0,m-1)x(n))x(n)).....x(n))x(n)),0,m-1)x(n)

f(0,0,2) = f(0,x)n

pretty much repeats for each added part of the sequence.

g(0)n = f(n,n,n,n,n..............n,n,n,n,n)n(n) with n n's.

g(1)n = f(n,n,n,n,n........,n,n,n))n(n) with (f(n,n,n,n,n..............n,n,n,n,n)n(n) with n n's) n's.

g(x)n = f(n,n,n,n,n..............n,n,n,n,n)n(n) with f(n,n,n,n,n..............n,n,n,n,n)n(n) with f(n,n,n,n,n..............n,n,n,n,n)n(n) with f(n,n,n,n,n..............n,n,n,n,n)n(n) with f(n,n,n,n,n..............n,n,n,n,n)n(n) with........... x layers of "with "g(x-1) n's" n's........f(n,n,n,n,n..............n,n,n,n,n)n(n) with n n's) n's) n's)......n's) n's.

from there on, g has the same pattern f does.

h(x)n = g(n,n,n,n,n..............n,n,n,n,n)n(n) with g(n,n,n,n,n..............n,n,n,n,n)n(n) with g(n,n,n,n,n..............n,n,n,n,n)n(n) with g(n,n,n,n,n..............n,n,n,n,n)n(n) with f(n,n,n,n,n..............n,n,n,n,n)n(n) with........... x layers of "with h(x-1) n's" n's........f(n,n,n,n,n..............n,n,n,n,n)n(n) with n n's) n's) n's)......n's) n's.

and all the letters after h repeat the same way.

now take VOID(0)x(n)y = f(n,n,n,n,n,n,n,n.......y n's.......n,n)x(n)

VOID(1)x(n)y = g(n,n,n,n,n,n,n,n.......y n's.......n,n)x(n)

VOID(2)x(n)y = h(n,n,n,n,n,n,n,n.......y n's.......n,n)x(n)

VOID(3)x(n)y = i(n,n,n,n,n,n,n,n.......y n's.......n,n)x(n)

and so on.

VOID(z)x(n)y is the z-th letter of the alphabet. if its after z(#)#, then it loops to a all the way to e. after e(#)# we ignore it as who cares if it can have a letter before it? we can just write 27(#)# and move on.

now do VOOID(m)z(x)n(y) = VOID(VOID(VOID......m layers....VOID(VOID(z)x(n)y))x(n)y))x(n)y))....x(n)y))x(n)y))

and VOOOID(h)m(z)x(n)y = VOOID(VOOID(.....h layers...VOOID(m)z(x)n(y))m(z)x(n)y))m(z)x(n)y)).....m(z)x(n)y))m(z)x(n)y))

VOOOOID does the same thing to VOOOID as VOOOID does to VOOID, etc.

overall the pattern repeats.

VO^xID(#)# represents VOOOOO...x o's....OOOOID(#)#.

VOID'S EPIC NUMBER IS EQUAL TO...

*epic drumroll*

VO^(666)ID(letter)#

(VoidSansXD's epic number is more like a range of numbers, really. the #'s means anything can go there.)

Advertisement